General aspects, host interaction, and application of Metarhizium sp. in arthropod pest and vector control - de Miranda, Rodrigo Prado Rodrigues; Soares, Talita Kellen dos Anjos; Castro, Daniele Pereira; Genta, Fernando Ariel (Frontiers in Fungal Biology, 2024)
The application of microorganisms as bio-control agents against arthropod populations is a need in many countries, especially in tropical, subtropical, and neotropical endemic areas. Several arthropod species became agricultural pests of paramount economic significance, and many methods have been developed for field and urban applications to prevent their, the most common being the application of chemical insecticides. However, the indiscriminate treatment based upon those substances acted as a selective pressure for upcoming resistant phenotype populations. As alternative tools, microorganisms have been prospected as complementary tools for pest and vectorial control, once they act in a more specific pattern against target organisms than chemicals. They are considered environmentally friendly since they have considerably less off-target effects. Entomopathogenic fungi are organisms capable of exerting pathogenesis in many vector species, thus becoming potential tools for biological management. The entomopathogenic fungi Metarhizium sp. have been investigated as a microbiological agent for the control of populations of insects in tropical regions. However, the development of entomopathogenic fungi as control tools depends on physiological studies regarding aspects such as mechanisms of pathogenicity, secreted enzymes, viability, and host-pathogen aspects. The following review briefly narrates current aspects of entomopathogenic fungi, such as physiology, cellular characteristics, host-pathogen interactions, and its previous applications against different insect orders with medical and economic importance. Approaches integrating new isolation, prospection, characterization, delivery strategies, formulations, and molecular and genetic tools will be decisive to elucidate the molecular mechanisms of EPFs and to develop more sustainable alternative pesticides.